2012
DOI: 10.3174/ajnr.a3137
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Standardized fMRI Reveals Altered Language Lateralization in Patients with Brain Tumor

Abstract: BACKGROUND AND PURPOSE:Brain tumors affecting language-relevant areas may influence language lateralization. The purpose of this study was to systematically investigate language lateralization in brain tumor patients using clinical language fMRI, comparing the results with a group of healthy volunteers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 55 publications
4
68
0
3
Order By: Relevance
“…High mean LIs of between 0.74 and 0.89 have been reported for sentence generation, both when sentences are pre-learnt prior to scanning (e.g., Stippich et al, 2003), and when they are actively generated during the scan (e.g., Tzourio- Mazoyer et al, 2016). However, other studies have reported more modest laterality estimates of between 0.48 and 0.65, again with both variants of the task (Mazoyer et al, 2014;Partovi et al, 2012a;Partovi et al, 2012b). Thus, it does not appear to be the case that strength of laterality differs according to whether sentences are generated spontaneously during the scanning session, or learnt prior to scanning.…”
Section: Strength Reliability and Robustnessmentioning
confidence: 84%
See 2 more Smart Citations
“…High mean LIs of between 0.74 and 0.89 have been reported for sentence generation, both when sentences are pre-learnt prior to scanning (e.g., Stippich et al, 2003), and when they are actively generated during the scan (e.g., Tzourio- Mazoyer et al, 2016). However, other studies have reported more modest laterality estimates of between 0.48 and 0.65, again with both variants of the task (Mazoyer et al, 2014;Partovi et al, 2012a;Partovi et al, 2012b). Thus, it does not appear to be the case that strength of laterality differs according to whether sentences are generated spontaneously during the scanning session, or learnt prior to scanning.…”
Section: Strength Reliability and Robustnessmentioning
confidence: 84%
“…Thus, it does not appear to be the case that strength of laterality differs according to whether sentences are generated spontaneously during the scanning session, or learnt prior to scanning. Two studies within our search measured laterality for semantic fluency and sentence generation within the same participants (Partovi et al, 2012a;Stippich et al, 2003); however, these studies reported differences in strength of laterality between the tasks in different directions. Further, they used the version of the sentence generation task in which sentences are learnt prior to scanning, so task demands were not well matched.…”
Section: Strength Reliability and Robustnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies on the feasibility of fMRI in presurgical mapping for brain tumors have been introduced [5]- [7] [16]. Because the fMRI study of cancer patients is difficult, SPAM-assisted presurgical mapping for brain tumor patients would be a more feasible option for clinics.…”
Section: Discussionmentioning
confidence: 99%
“…For example, functional magnetic resonance imaging is used to assess laterality in preoperative brain tumor cases [5]- [7]. In addition, navigated transcranial magnetic stimulation (nTMS) is increasingly used in presurgical brain mapping.…”
Section: Introductionmentioning
confidence: 99%